Archives and Resources in the Thames Region for Twentieth- and Twenty-First-Century Environmental History. (November 2015) - Palmer, Sarah Rosalind
Abstract : There is a wealth of fascinating historical material — much of it unknown or underutilized — available for research into Thames environmental history. This paper, focusing particularly on the last fifty years, provides a brief introduction to the types and range of historical resources, held in record offices and archives across the region, which can be used to illuminate our understanding of the ways in which this important river has shaped the lives of Londoners and the other communities along its banks.